The public sphere in the Polish Prime Ministers’ exposés 1989-2012 - Płaneta, Paweł (Journal of Public Governance, 2014)
The main aim of the paper is to present the results of the survey on the axiological sphere of the government programme addresses (exposés) of the Polish Prime Ministers in 1989-2012. The first step of the analysis is the lexical analysis of the speeches gathered in the text corpus. The results of statistical evaluations are word frequency lists which are used for the analysis of certain word concordances and collocations. The effect is the reconstruction of common patterns of important word co-occurrences. In this phase of the survey, the units of analysis are words, so the intensity of the analyzed text attributes is measured by the number and percentage range of certain words. The next phase of the survey is computer-assisted content analysis. For the research purposes, dictionaries of the categories were createdwhich consisted of sets of words with the same semantic basis. The unit of analysis in this phase is a sentence, and the result of the analysis is a hierarchy and ‘keyness’ of collective symbols in the Prime Ministers’ speeches. The result of the next phase is an axiological map of the discourse of values in the analyzed exposés. In the last part of the research, as a result of factor analysis, the structure of the discourse is reduced to several strongest factors determining which different (detailed) categories have the tendency to co-occur and therefore create easily distinguishable configuration of miranda (i.e. what we should admire, adore, love, fight for, support) and condemnanda (i.e. what we should condemn, hate, fight against) representing various values (and anti-values) in the exposés of Polish Prime Ministers.